3(X-5)+4(2X+1)=9

Simple and best practice solution for 3(X-5)+4(2X+1)=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(X-5)+4(2X+1)=9 equation:


Simplifying
3(X + -5) + 4(2X + 1) = 9

Reorder the terms:
3(-5 + X) + 4(2X + 1) = 9
(-5 * 3 + X * 3) + 4(2X + 1) = 9
(-15 + 3X) + 4(2X + 1) = 9

Reorder the terms:
-15 + 3X + 4(1 + 2X) = 9
-15 + 3X + (1 * 4 + 2X * 4) = 9
-15 + 3X + (4 + 8X) = 9

Reorder the terms:
-15 + 4 + 3X + 8X = 9

Combine like terms: -15 + 4 = -11
-11 + 3X + 8X = 9

Combine like terms: 3X + 8X = 11X
-11 + 11X = 9

Solving
-11 + 11X = 9

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 11X = 9 + 11

Combine like terms: -11 + 11 = 0
0 + 11X = 9 + 11
11X = 9 + 11

Combine like terms: 9 + 11 = 20
11X = 20

Divide each side by '11'.
X = 1.818181818

Simplifying
X = 1.818181818

See similar equations:

| 3x^2-32x-11= | | H(x)=-16x^2+16x+5 | | v^2-2v+8=0 | | 9x+y=11 | | 15b^2+12b^3= | | (-10)(3000)= | | 4y^2+3x-24y-12=0 | | 12m-13=9m+38 | | 57+12m=7m+149 | | 13x+1=5x+49 | | 97+13m=5+17m | | 8y^2-y=-9 | | 11x=3x-56 | | 3x+9-7x=33 | | 5-y=10y-40 | | -3=4(-3)+6-(-3) | | 141000000/1.17 | | 6x+2-3x+2=9x-12 | | 9-5/3b=3 | | 2x^2-8x+8=98 | | 5(2+X)=3x-4 | | x^2/4x | | u^2-10u-21=0 | | 2x+4/3=x/7 | | 10+10M=0.35M | | 3m+71=11m+15 | | (u^2-8u-12)2=0 | | 14m+6=9m+91 | | 26x^2-30x-1147=0 | | 5-(2x-3)=-3+6 | | 9/30 | | 183-2m=4m |

Equations solver categories